Conditions of outsourcing implementation in e-business - Sobińska, Małgorzata (Uwarunkowania implementacji outsourcingu w e-biznesie, 2020)
The article deals with an issue very closely related to contemporary management practice, namely e-business outsourcing. Currently, organizations, perhaps especially those running a business online, are not able to meet all the needs and requirements dictated by dynamically changing conditions on their own, and more and more often decide to cooperate with the network in order to ensure access to appropriate resources, including skills, knowledge, qualifications and technology. Outsourcing has become one of the most effective management tools – a cheap and effective way to share and use global resources. The paper attempts to demonstrate that outsourcing plays an important role in the functioning of e-business models, with a particular emphasis on e-commerce models. The aim of the article was also to indicate the most important benefits and threats related to cooperation with external IT service providers, to define the course of the outsourcing process and the requirements that should be met by companies that decide on such a model of operation, so that the cooperation could run smoothly and bring the expected results
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 4 (58), s. 142-157
Keywords: informatyka ekonomiczna